Penentuan Kadar Flavonoid Total dan Klasifikasi Serbuk Daun Murbei (Morus alba L.) Berbeda Ketinggian Tempat Tanam - Syaifullah, Abim; Kristiningrum, Nia; Pangaribowo, Dian Agung; Wulandari, Lestyo (Faculty of Pharmacy, University of Jember, 2024)
Mulberry (Morus alba L.) is a plant from the Moraceae family which has a high flavonoid content. This research aims to determine the ability of NIR spectroscopy and chemometrics to classify mulberry leaf powder based on different planting heights and determine the total flavonoid content using the Uv-Vis spectrophotometric method. The classification of mulberry leaf powder originating from the lowlands, midlands, and highlands provides valid results using NIR spectra and chemometric data from the LDA and SIMCA models with an accuracy value of 100%. The average results of determining total flavonoid content using Uv-Vis spectrophotometry showed that the highest levels were in the highlands, followed by the medium and lowlands with total flavonoid levels respectively, namely 6.453 ± 1.194 mg QE/g powder; 5.889 ± 0.944 mg QE/g powder; and 5.177 ± 0.998 mg QE/g powder. The results of the One Way ANOVA test showed that the total flavonoid content of mulberry leaf powder from different altitude areas did not have a significant difference.